2007
DOI: 10.1080/14659890600823826
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment utilization before, during and after pregnancy

Abstract: This study retrospectively explored drug treatment utilization before, during and after pregnancy for all identified substance-using women delivering at a county hospital over a 4-year period (n=431). Drug treatment data were linked to hospital data to analyse treatment utilization. Fifty-three per cent received treatment the year before, during, or within the year after delivery, with a significantly higher proportion receiving treatment during and after pregnancy. There were significant increases in methadon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous research has found that >50% of pregnant women who need SUD treatment receive it only during the postpartum period. 57 This finding highlights the need for programs that can provide ongoing services to ensure that parents achieve long-term recovery, which is pivotal for early childhood development.…”
Section: Role Of Parental Treatmentmentioning
confidence: 97%
“…Previous research has found that >50% of pregnant women who need SUD treatment receive it only during the postpartum period. 57 This finding highlights the need for programs that can provide ongoing services to ensure that parents achieve long-term recovery, which is pivotal for early childhood development.…”
Section: Role Of Parental Treatmentmentioning
confidence: 97%
“…[2][3][4] The use of medications for the treatment of OUD has been associated with improvements in prenatal care adherence and pregnancy outcomes, including lower rates of preterm birth and low birth weight and reductions in maternal relapse and overdose. 2,[5][6][7] Although pregnancy provides a motivational opportunity for women with OUD to initiate treatment with medication to engage in care and increase their engagement with health care services, 8 only 50% to 60% of pregnant women with OUD use any medication for the treatment of OUD. [9][10][11] The underuse of medication for the treatment of OUD in the general population has been attributed to a shortage of treatment programs and clinicians offering medications for OUD, insufficient insurance coverage of services, and persistent stigma and misunderstanding about the use of medications for the treatment of OUD.…”
Section: Introductionmentioning
confidence: 99%
“…The use of medications for the treatment of OUD has been associated with improvements in prenatal care adherence and pregnancy outcomes, including lower rates of preterm birth and low birth weight and reductions in maternal relapse and overdose . Although pregnancy provides a motivational opportunity for women with OUD to initiate treatment with medication to engage in care and increase their engagement with health care services, only 50% to 60% of pregnant women with OUD use any medication for the treatment of OUD …”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that substance abuse treatment is effective in decreasing substance use and improving birth outcomes for pregnant women who attend treatment (McMurtrie et al 1999). Rates of drug treatment entry increase during pregnancy (Wolfe et al, 2007) but retaining pregnant women in treatment can be difficult (Haller et al, 1997) and therefore increasing treatment utilization has been identified as an important goal for programs treating pregnant substance users (Howard and Beckwith, 1996). Even small increases in compliance with drug treatment have been associated with improved maternal and infant outcomes (Jones, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%